Visuotactile learning and body representation: an ERP study with rubber hands and rubber objects. - Press, C; Heyes, C; Haggard, P; Eimer, M (2008)
We studied how the integration of seen and felt tactile stimulation modulates somatosensory processing, and investigated whether visuotactile integration depends on temporal contiguity of stimulation, and its coherence with a preexisting body representation. During training, participants viewed a rubber hand or a rubber object that was tapped either synchronously with stimulation of their own hand, or in an uncorrelated fashion. In a subsequent test phase, somatosensory event-related potentials (ERPs) were recorded to tactile stimulation of the left or right hand, to assess how tactile processing was affected by previous visuotactile experience during training. An enhanced somatosensory N140 component was elicited after synchronous, compared with uncorrelated, visuotactile training, irrespective of whether participants viewed a rubber hand or rubber object. This early effect of visuotactile integration on somatosensory processing is interpreted as a candidate electro-physiological correlate of the rubber hand illusion that is determined by temporal contiguity, but not by preexisting body representations. ERP modulations were observed beyond 200 msec poststimulus, suggesting an attentional bias induced by visuotactile training. These late modulations were absent when the stimulation of a rubber hand and the participant's own hand was uncorrelated during training, suggesting that preexisting body representations may affect later stages of tactile processing.